High electric current and hours can increase layer thickness and decrease white rust corrosion using Zn2+ electroplating - Slamet Riyadi; Yanuar Zulardiansyah Arief; Antonius Darma Setiawan; Agung Pangestu; Rosyid Ridlo Al-Hakim (Journal of Technology Informatics and Engineering, 2022)
Electroplating was the process of coating metal surfaces using the electrochemical method. We used alkaline zinc (Zn2+) plating that was anti-corrosion coating, cheapest, evenly adhesion, as well as better-looking crushing. This study aims to test and measure the thickness of the layer on spark plugs with variations in different electrical currents 300, 400, and 500A and increased hours during the coating process, investigate the corrosion resistance of white rust on the surface and analyze the changes in alkaline zinc concentration and temperature that affect the thickness of the layer, respectively. The results, such as 1st sample 13 pcs, 300A, and thickness of 7.26-micron with white rust 9 pcs. 2nd sample 13 pcs, 400A, and thickness of 9.15-micron white rust 5 pcs. 3rd sample 13 pcs, 500A, and thickness of 12.75-micron white rust 3 pcs. The high electric current (500A) and 45 hours of the experiment would influence the lowest white rust corrosion level. The high alkaline zinc solution with an optimum 36°C solution temperature and 500A electric current would undoubtedly deposit the white rust until 3 pcs.